The Influence of Solid Palm Oil Waste and Npk Fertilizer on the Growth and the Production of Green Eggplant (Solanum MelongenaL.) (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this research was to discover the effect of solid and NPK fertilizer, as well as the interaction of solid and NPK fertilizer on the growth and production of green eggplant. This research used a factorial randomized block design with two treatment factors, namely the first factor: Administrationof oil palm solid which consisted of 4 levels of treatment, namely: S0 = No palm oilwaste solid; S1 = Administration of palm oil waste solid at 0.5 kg/m2; S2 = Administration of palm oil waste solid at 1 kg/m2; S3 = Administration of palm oil waste solid at 1.5 kg/m2. The second factor is the addition of NPK fertilizer per plant (J) consisting of 3 levels of treatment, namely: J0 = 0 g/plant; J1 = 5 g/plant; J2 = 10 g/plant. The results showed that solid treatment significantly affected the plants height at ages 2, 4, and 6 MST, flowering age, production per plant, and production per plot. The treatment of Solid S3 produced the highest plants aged 2, 4, and 6 MST, respectively (21.78 cm), (53.45 cm), and (77.78 cm), the fastest flowering age (32.89 days), highest production per plant (1748.77 g), and highest production per plot (21.89 kg). The NPK treatment significantly affected the plants height at ages 4 and 6 WAP, flowering age, production per plant, and production per plot. The NPK J2 fertilizer dosage treatment produced the highest plants aged 4 and 6 WAP, respectively (47.83 cm), and (75.84 cm), the fastest flowering age (32.91 days), the highest production per plant (1562.91 g), and the highest production per plot (19.86 kg). The interaction treatment of the NPK fertilizer and solid administration did not significantly affect all parameters. The combination of S3J2 produced the highest plants aged 2 and 6 WAP, respectively (22.33 cm) and (79.67 cm), the fastest flowering age (32.33 days), the highest production per plant (1816.67 g), the and highest production per plot (22.49 kg).